Aligning performance: The end of personnel and the beginning of guided skilled performance - David H. Tobey; Philip G. Benson (Management Revue, 2009)
For almost twenty years researchers have predicted the end of personnel as HRM practices increasingly became a line management function. However, while useful for describing shifts in human resource responsibilities, this practice-based view obscures the fundamental strategic reason for this shift - executive demands for effective means to manage performance. This paper contributes a new approach for HRM that may better predict which current practices will be most successful and suggests the characteristics of new practices that may be developed using an example of goalsetting and performance appraisal. The theory includes a model of human performance based on recent advances in cognitive neuroscience that suggests HRM may fulfill a strategic role by reestablishing its core competence as specialists in industrial psychology who create systems for guiding skilled performance. We conclude by proposing a measure that assesses the link between performance and customer perceived value across the value chain, thereby demonstrating the return on investment in human resources.
Keywords: 650; SHRM; cognitive neuroscience; performance management